Auditoría de gestión basada en el modelo de evaluación de las extensiones en la U.T.C. cantón La Maná - Jami Jami, Mónica Karina (2016)
This research aims to analyze the impact of the implementation of a management audit as part of the evaluation of university offices in order to assess the level of trust in information, in addition to examining the involvement of resource planning and analyze compliance with the legal base, in the first instance, there are theoretical scientific information from some authors, subsequently the analyzing of survey conducting the analysis and interpretation of results with their respective conclusions and recommendations for the research field, used the proper technological support for the development of statistical tables and charts, in carrying out the proposed audit process is carried out through the following phases: the first phase is the preliminary knowledge where the report situational analysis of the company is made, the second phase consists of the file permanently....